Huwe1 interacts with Gadd45b under oxygen-glucose deprivation and reperfusion injury in primary Rat cortical neuronal cells. Issue 1 (December 2015) - He, Guo-qian; Xu, Wen-ming; Li, Jin-fang; Li, Shuai-shuai; Liu, Bin; Tan, Xiao-dan; Li, Chang-qing
Abstract Background Growth arrest and DNA-damage inducible protein 45 beta (Gadd45b) is serving as a neuronal activity sensor. Brain ischemia induces the expression of Gadd45b, which stimulates recovery after stroke and may play a protective role in cerebral ischemia. However, little is known of the molecular mechanisms of how Gadd45b expression regulated and the down-stream targets in brain ischemia. Here, using an oxygen-glucose deprivation and reperfusion (OGD/R) model, we identified Huwe1/Mule/ARF-BP1, a HECT domain containing ubiquitin ligase, involved in the control of Gadd45b protein level. In this study, we also investigated the role of Huwe1-Gadd45b mediated pathway in BDNF methylation. Results We found that the depletion of Huwe1 by lentivirus shRNA mediated interference significantly increased the expression of Gadd45b and BDNF at 24 h after OGD. Moreover, treatment with Cycloheximide (CHX) inhibited endogenous expression of Gadd45b, and promoted expression of Gadd45b after co-treated with lentivirus shRNA-Huwe1. Inhibition of Gadd45b by lentivirus shRNA decreased the expression levels of brain derived neurotrophic factor (BDNF) and phosphorylated cAMP response element-binding protein (p-CREB) pathway, while inhibition of Huwe1 increased the expression levels of BDNF and p-CREB. Moreover, shRNA-Huwe1 treatment decreased the methylation level of the fifth CpG islands (123 bp apart from BDNF IXa), while shRNA-Gadd45b treatment increased the methylation level of the forth CpG islands (105 bp apart from BDNF IXa). Conclusions These findings suggested that Huwe1 involved in the regulation of Gadd45b expression under OGD/R, providing a novel route for neurons following cerebral ischemia-reperfusion injury. It also indicated that the methylation of BDNF IXa was affected by Gadd45b as well as Huwe1 in the OGD/R model.